G239(P) Updates by Email, a Thing of the Past? Cloud Sharing Revolutionises Rota Management. (24th May 2017) - Rajamoorthy, V; Sheth, P; Merchant, N
Abstract : Doctors' rotas are often notoriously difficult to manage and update. The Rota Coordinators at this hospital introduced a way of storing and updating the rota for the Registrars on Dropbox, which is a free file sharing cloud. We opened accounts for all the Registrars at the start of the academic year and provided access to a single folder where the rota was stored. All updates were done in this central folder. Previously, the file was stored on the hospital network and updates were emailed to everyone, sometimes daily. This meant, updates were only possible when at the hospital. We found regular emails to be time consuming and often, the up to date version would be lost among other emails. Our new method provided accessibility to the Rota Coordinators both at home and work, as well as providing smartphone access. Hence, responding to rota related queries was quicker, which would otherwise have needed to wait until the next shift at the hospital. It also reduced the need for multiple emails which was time consuming and repetitive. Updates were available to be viewed instantaneously, hence ensuring accuracy. We sent out a survey on Survey Monkey to 14 Registrars to provide feedback on this new method. Stage of training among trainees who participated Accessibility of the rota in Dropbox Preference to keep the rota on Dropbox or get regular updates by email Rota queries being answered in a timely manner due to the improved accessibility There is a need to update and find new ways to improve services that have previously always proved to be a challenge. We found Dropbox to be generally well accepted by the team and suggest it to be trialled in other departments and hospitals.